(untitled) (Eurasian Medical Research Periodical, 2022)
Spirituality has always been, in all times, primarily serving human perfection, the development of noble qualities in the hearts of people. Most importantly, spirituality was a great power in creating a new spiritual and spiritual space based on the unity and solidarity of the people, enriching the life of society with new noble ideas. It is this space that has created a new wave of awakening, which strengthens the spirit of nationalism, patriotism in the hearts and minds of people and leads society to a higher path of development. Today, the glorious goal” from the national revival – towards the National upsurge " was put on the agenda. Based on the requirements of the new period of development, the most important tasks that will be carried out in our country have been identified. In this article, opinions and comments are made about the theoretical and methodological problems of creating a spiritual space in Uzbekistan.